2022
DOI: 10.1111/ecog.06140
|View full text |Cite
|
Sign up to set email alerts
|

Biogeographic deconstruction of phylogenetic and functional diversity provides insights into the formation of regional assemblages

Abstract: Evolutionary history and environmental filtering shape the phylogenetic and functional structure of regional assemblages. However, detecting the footprint of such eco-evolutionary drivers is challenging because these may often counter each other's signature. Here, we examined whether a biogeographic deconstruction approach of phylogenetic (PD) and functional diversity (FD) patterns may help in identifying ecoevolutionary signals in extant regional assemblages. As model system, we used forest understorey angios… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 57 publications
1
9
0
Order By: Relevance
“…We found that the phylogenetic diversity (PD) was highly correlated, and showed a similar geographical pattern to that of the RE (r = 0.72; Figures S3 and S4 ). The correlation between the PD and RE is a common pattern [ 14 , 24 , 26 , 33 , 88 , 89 , 90 ] but, as other studies pointed out [ 19 , 26 , 91 ], the PE and sesPD were not highly correlated with the RE (r = 0.50 and 0.23, respectively; Figure S3 ), and the sesPD was not correlated with the PD (r = 0.38; Figure S3 ), but was more correlated with the PE (r = 0.69; Figure S3 ), because the PE accounts for the spatial distribution of the species, and the sesPD is standardised according to species diversity. Hence, areas of high species richness are not always areas with a high phylogenetic diversity or phylogenetic endemism [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…We found that the phylogenetic diversity (PD) was highly correlated, and showed a similar geographical pattern to that of the RE (r = 0.72; Figures S3 and S4 ). The correlation between the PD and RE is a common pattern [ 14 , 24 , 26 , 33 , 88 , 89 , 90 ] but, as other studies pointed out [ 19 , 26 , 91 ], the PE and sesPD were not highly correlated with the RE (r = 0.50 and 0.23, respectively; Figure S3 ), and the sesPD was not correlated with the PD (r = 0.38; Figure S3 ), but was more correlated with the PE (r = 0.69; Figure S3 ), because the PE accounts for the spatial distribution of the species, and the sesPD is standardised according to species diversity. Hence, areas of high species richness are not always areas with a high phylogenetic diversity or phylogenetic endemism [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Usually clustering/overdispersion patterns are not identified over a whole studied region but within each local area in reference to a large delimited region (e.g., Molina-Venegas et al, 2022; Ramm et al, 2018; Rocha et al, 2019; Yang et al, 2014). Their identification has so far required the use of null models and randomization of species occurrences or FP characteristics (e.g., Hardy & Senterre, 2007; Webb et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…The randomization procedure was repeated 9999 times to compare if a significant difference existed between observed and random PD (Borko et al., 2022). Values of sesPD >1.96 indicate a significantly higher PD than expected (random PD) at a given level of species richness, and values below −1.96 indicate a significantly lower PD (Molina‐Venegas et al., 2022). Faith's PD and sesPD were implemented in the ‘picante’ R package (Kembel et al., 2010).…”
Section: Methodsmentioning
confidence: 99%